Visual association encoding activates the medial temporal lobe: A functional magnetic resonance imaging study - Rombouts, Serge A.R.B.; Machielsen, Willem C.M.; Witter, Menno P.; Barkhof, Frederik; Lindeboom, Jaap; Scheltens, Philip (Hippocampus, 1997)
The involvement of structures in the medial temporal lobe during the encoding of visual associations was studied with functional magnetic resonance imaging. In 11 out of 12 normal healthy volunteers this task resulted in activation in posterior portions of the parahippocampal region, close to the collateral sulcus. In seven subjects activation was encountered in the hippocampal formation. The visual association task as adapted for this study may provide a sensitive measure to study anterograde amnesia prevalent in Alzheimer's disease. Therefore, the present paradigm enables the study of individual changes in learning and memory capacities over time. Hippocampus 1997;7:594–601. © 1997 Wiley‐Liss, Inc.